Indoleamine 2,3-dioxygenase (IDO) Activity in Placental Compartments of Renal-Transplanted Pregnant Women - Prado, Karen Matias do; Correa-Silva, Simone [UNESP]; Oliveira, Leandro Gustavo de [UNESP]; Saraiva Camara, Niels Olsen; Ono, Erica; Sandri, Silvana; Tourino, Melissa Cavalheiro; Campa, Ana; Lima, Larissa de Sa; Scavone, Cristoforo; Bevilacqua, Estela (Wiley-Blackwell, 2014)
Problem Immunosuppressive drugs change gestational IDO activity at the maternal-fetal interface. Method of Study Analysis of placental IDO expression and activity, interferon gamma (IFN-), and IL-10 expression and NFkB activity in renal transplant recipient women under immunosuppressive treatment. Results We demonstrated a significant reduction in IDO activity (P=0.0275) and expression (P=0.026) and in NFkB activity (P=0.0176) in the villous region of renal transplanted mother. These findings did not correlate with the higher serum levels of kynurenine (P=0.002). In the decidual compartment, IDO was immunolocalized mainly on the extravillous cytotrophoblast but did not show significant differences among the experimental groups; kynurenine was significantly higher (P=0.036) and was inversely proportional to the decidual IFN- profile (P=0.0433). No change was seen in IL-10 levels. NFkB activity was significantly higher in decidual compartment correlating with the higher IDO activity and suggesting that in immunosuppressant pregnancy, IDO activity and expression remain regulated by NFkB. Conclusion The increased IDO activity in decidua may indicate an attempt to offset the low expression. These findings call attention to the relevance of IDO activity at the maternal interface in pregnant transplant recipients, likely modulated by immunosuppressive agents and associated with a high risk of associated gestational disorders.
Keywords: IDO; IFN-; Immunosuppressive drugs; Kynurenine; NF-B; Placenta